Alleviation of ammonia inhibition via nano-bubble water supplementation during anaerobic digestion of ammonia-rich swine manure: Buffering capacity promotion and methane production enhancement. (August 2021) - Fan, Yujie; Yang, Xiaojing; Lei, Zhongfang; Zhang, Zhenya; Kobayashi, Motoyoshi; Adachi, Yasuhisa; Shimizu, Kazuya
Highlights: Ammonia inhibition was alleviated under nano-bubble water (NBW) supplementation. Extracellular hydrolases and coenzyme F420 were enhanced with NBW supplementation. NBW supplementation promoted buffering capacity under ammonia inhibition. CH4 production was enhanced by 12.3–38.7% by NBW supplementation. NBW addition shortened the lag phase and increased the maximum CH4 production rate. Abstract: Anaerobic digestion (AD) of ammonia-rich swine manure (SM) with nano-bubble water (NBW) supplementation was studied in this work with the expectation of ammonia inhibition alleviation, buffering capacity promotion, and methane production enhancement. Results indicated that cumulative methane yield was elevated by 12.3–38.7% in NBW groups. Besides, the reduced methane production rate and elongated lag phase under ammonia inhibition were increased and shortened by NBW supplementation, respectively. The rapid increase of total alkalinity (TA) and partial alkalinity (PA) could be observed with NBW supplementation, as well as the rapid decline of VFA/TA, thus improved buffering capacity and alleviated ammonia inhibition. Moreover, higher level of extracellular hydrolases and coenzyme F420 could be detected in NBW groups. In conclusion, NBW with higher mobility and zeta potential (absolute value) could be a promising strategy for the alleviation of ammonia suppression during the AD of SM.